Social Protection at the Humanitarian-Development Nexus : Insights from Yemen - Ghorpade, Yashodhan (World Bank, Washington, DC, 2021)
In its seventh year of conflict, facing successive shocks and a heightened risk of famine, Yemen has been termed the world’s ‘worst humanitarian crisis.’ Against this backdrop, there has been a drastic transformation of Yemen’s social protection landscape, with the disruption of several governmental SP programs, the continued functioning of some national institutions and a massive increase in humanitarian assistance programs. In this paper, authors first review conceptual differences between humanitarian and development assistance along several features, also noting the blurring of sharp distinctions. The authors then assess the institutional landscape of social assistance in Yemen, using a unique dataset authors collated using administrative data from a range of humanitarian and development agencies. The authors compare programs in terms of scale, geographical coverage, average benefit levels, and targeting. The authors find that while there are important differences between humanitarian and development approaches, there are also many areas of convergence. While the total number of people covered by all humanitarian and development assistance programs exceeds the national population, authors also find evidence of likely exclusion of many poor households, suggesting that there is significant scope to reduce exclusion through improved coordination. The paper concludes with a discussion of areas and specific proposals for enhanced humanitarian-development coordination in the social assistance space at the strategic, program, and delivery-systems levels.